The influence of austenitising temperature on the microstructure and mechanical properties of low-alloyed Ni-Mo-Cu austempered ductile iron - Radulović, Branko (Materiali in tehnologije, 2000)
In the present study we have investigated the effect of austenitising temperature and austempering time on the microstructure and mechanical properties of low-alloyed Ni-Mo-Cu ductile iron. The specimens were austenised at 850, 875, 900 and 930°C for 120 min, then austempered for 10, 30,60, 120, 240 and 360 min at 350°C, and examined by optical and scanning electron microscopy. The volume fraction of retained austenite, bainite, martensite and austenite-carbon content results were then correlated with microstructural changes, the kinetics of transformation and impact toughness. Following short periods of austempering time, the carbon content of the retained austenite is low and on subsequent cooling to room temperature it transforms to martensite, resulting in low impact values. The carbon content of the austenite was evaluated by measuring the latice parameters using X-ray diffraction. Optimum properties were obtained at 900°C for intermediate austempering periods (120-240 min).
Keywords: litine; avstenit; tempranje; vpliv temperature; mehanske lastnosti